GOVERNMENT RELATIONS STATUS REPORT (Tufts Archival Research Center, 2007)
Letter from Gene Ainsworth to Dolph von Arx regarding the May 1988 Government Relations Status Report. Summarizes legislative activity on the in the federal, state and local level. Includes information on the airline smoking ban, increases in cigarette excise taxes and various ballot initiatives.